2012
DOI: 10.1051/0004-6361/201219845
|View full text |Cite
|
Sign up to set email alerts
|

Staring at 4U 1909+07 withSuzaku

Abstract: We present an analysis of the neutron star high mass X-ray binary (HMXB) 4U 1909+07 mainly based on Suzaku data. We extend the pulse period evolution, which behaves in a random-walk like manner, indicative of direct wind accretion. Studying the spectral properties of 4U 1909+07 between 0.5 to 90 keV we find that a power-law with an exponential cutoff can describe the data well, when additionally allowing for a blackbody or a partially covering absorber at low energies. We find no evidence for a cyclotron reson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 24 publications
7
19
0
Order By: Relevance
“…The addition of high energy cut-off to the partial covering power-law model fitted data well with the black-body temperature of ∼0.2 keV. The parameters obtained by fitting the partial covering high energy cut-off power-law model to the spectrum are in good agreement with Table 2 of Fürst et al (2012). However, the partial covering NPEX continuum model with iron line and black-body component described the spectrum better yielding an acceptable black-body temperature of 0.2 keV.…”
Section: Spectral Analysissupporting
confidence: 72%
See 2 more Smart Citations
“…The addition of high energy cut-off to the partial covering power-law model fitted data well with the black-body temperature of ∼0.2 keV. The parameters obtained by fitting the partial covering high energy cut-off power-law model to the spectrum are in good agreement with Table 2 of Fürst et al (2012). However, the partial covering NPEX continuum model with iron line and black-body component described the spectrum better yielding an acceptable black-body temperature of 0.2 keV.…”
Section: Spectral Analysissupporting
confidence: 72%
“…The pulse profile was found to be strongly energy dependent. The phase averaged spectrum, obtained from above observations, were well described by a power-law with high energy cut-off continuum model along with a black-body component (Fürst et al 2011). Fürst et al (2012 also analyzed data from Suzaku observation of the pulsar and described the spectrum using same model as was used in case of their earlier work.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Long term timing studies showed that the spin period of the pulsar changes erratically on years time scale. It is only possible when mass accretion through the capture of stellar wind occurs in the system (Fürst et al 2011(Fürst et al , 2012. A similar conclusion was drawn based on the detection of the Compton shoulder in the iron fluorescence line.…”
Section: Introductionmentioning
confidence: 75%
“…We constructed radial profiles for the three observations of Vela X-1 (Fürst et al 2014) for the energy bands used above, and compared the radial profiles directly for each radial bin. We subtracted the late-time profiles from the reference profile (T=0, obs.…”
Section: Off-axis Psfmentioning
confidence: 99%